Work-life balance as a predictor of organizational commitment: a multidimensional approach - Stefanus Rumangkit; Z Zuriana (Diponegoro International Journal of Business, 2019)
The article investigates the relationship between dimensions of work-life balance (time balance, involvement balance, and satisfaction balance) on organizational commitment. Employee at one of the hotels in Bandarlampung, Lampung, Indonesia, were surveyed and a total of 60 useable questionnaires were returned. We employed multiple regression analysis on those data and found that the time balance, involvement balance, and satisfaction balancepositively affected the organizational commitment.